Making Your Community Green: Community-Based Social Marketing for EcoFriendly Communities - Krystal K. Noiseux; Mark E. Hostetler (EDIS, 2008)
WEC-240, a 6-page illustrated fact sheet by Krystal K. Noiseux and Mark E. Hostetler, provides information and strategies for motivated homeowners to engage their neighbors to address local environmental issues. Published by the UF Department of Wildlife Ecology and Conservation, November 2007.